A rare case of carcinoma rectum with scalp metastasis: an unusual presentation - Abraham, Amal; K., Krishnaprasad; G. P., Praveen; Vikas, Shankar; N., Keerthi (International Surgery Journal, 2018)
Colorectal cancer is the third most commonly diagnosed cancer and third leading cause of cancer death in both men and women in the world. Metastasis is common in case of carcinoma rectum due to the late arrival of the patient to the doctor. The common sites for metastasis are liver, lung or ovary. But metastasis to the scalp is very rare. A 65-year-old female patient who presented to the casualty with sub-acute intestinal obstruction of four days duration was managed conservatively. Incidentally the patient noticed a swelling over the scalp which was initially of size 1 × 1 cm which progressed to the size of 3 × 3 cm over a period of 2 weeks. FNAC from the swelling showed features of skin adnexal tumor. Excision of the swelling was done, and histopathological examination revealed features of metastatic adenocarcinoma. Colorectal carcinoma can be controlled or treated with frequent screening of any individual who has crossed 50 years with occult stool for blood or by colonoscopy. In this way metastasis can be controlled if we treat at the early stages.